Stakeholder’s perspectives on acceptable interventions for promoting hypertension medication adherence in Namibia: nominal group technique - Tafadzwa Dzinamarira; Tivani Phosa Mashamba-Thompson; Benn Sartorius; Olivia Nakwafila; Tonderai Washington Shumba (BMJ Open, 2023)
Objective To determine the most acceptable hypertension intervention package to promote hypertension adherence based on stakeholders’ perspectives.Design We employed the nominal group technique method and purposively sampled and invited key stakeholders offering hypertension services and patients with hypertension. Phase 1 was focused on determining barriers to hypertension adherence, phase 2 on enablers and phase 3 on the strategies. We employed the ranking method based on a maximum of 60 scores to establish consensus regarding hypertension adherence barriers, enablers and proposed strategies.Setting and participants 12 key stakeholders were identified and invited to participate in the workshop in Khomas region. Key stakeholders included subject matter experts in non-communicable diseases, family medicine and representatives of our target population (hypertensive patients).Results The stakeholders reported 14 factors as barriers and enablers to hypertension adherence. The most important barriers were: lack of knowledge on hypertension (57 scores), unavailability of drugs (55 scores) and lack of social support (49 scores). Patient education emerged as the most important enabler (57 scores), availability of drugs emerged second (53 scores) and third having a support system (47 scores). Strategies were 17 and ranked as follows: continuous patient education as the most desirable (54 scores) strategy to help promote hypertension adherence, followed by developing a national dashboard to primarily monitor stock (52 scores) and community support groups for peer counselling (49 scores).Conclusions Multifaceted educational intervention package targeting patient and healthcare system factors may be considered in implementing Namibia’s most acceptable hypertension package. These findings will offer an opportunity to promote adherence to hypertension therapy and reduce cardiovascular outcomes. We recommend a follow-up study to evaluate the proposed adherence package’s feasibility.